FINANCIAL SECURITY AND PUBLIC DEBT - Ismailova Nasiba Komildjanovna (Ecominds Press, 2025)
This article is dedicated to the socio-economic essence of financial security, its indicators, and the degree of protection of financial interests at the macro level. It analyzes financial security indicators in the country, including the relationship between the budget deficit and the volume of imports with the country's gold and foreign exchange reserves, the current state of public debt, and its impact on the national financial security system. Additionally, attention is given to addressing the existing challenges in the financial security system of the Republic of Uzbekistan.
Keywords: Economic stability, economic security, financial security, financial security indicators, budgetary security, budget deficit, gold and foreign exchange reserves, investment volume, inflation rate, external public debt.